Electric machinery fundamentals - Chapman, Stephen J. (McGraw-Hill Higher Education, 2012)
Electric Machinery Fundamentals continues to be a best-selling machinery text due to its accessible, student-friendly coverage of the important topics in the field. In the fifth edition, the use of MATLAB (R) continues to be incorporated in examples and problems, where applicable.